Evaluation of fecal sample collection methods for feline gut microbiome profiling: fecal loop vs. litter box - Ma, Xiaolei; Brinker, Emily; Lea, Christopher R.; Delmain, Diane; Chamorro, Erin D.; Martin, Douglas R.; Graff, Emily C.; Wang, Xu (Frontiers in Microbiology, 2024)
Introduction Microbial population structures within fecal samples are vital for disease screening, diagnosis, and gut microbiome research. The two primary methods for collecting feline fecal samples are: (1) using a fecal loop, which retrieves a rectal sample using a small, looped instrument, and (2) using the litter box, which collects stool directly from the litter. Each method has its own advantages and disadvantages and is suitable for different research objectives. Methods and results Whole-genome shotgun metagenomic sequencing were performed on the gut microbiomes of fecal samples collected using these two methods from 10 adult cats housed in the same research facility. We evaluated the influence of collection methods on feline microbiome analysis, particularly their impact on DNA extraction, metagenomic sequencing yield, microbial composition, and diversity in subsequent gut microbiome analyses. Interestingly, fecal sample collection using a fecal loop resulted in a lower yield of microbial DNA compared to the litterbox method (p = 0.004). However, there were no significant differences between the two groups in the proportion of host contamination (p = 0.106), virus contamination (p = 0.232), relative taxonomy abundance of top five phyla (Padj > 0.638), or the number of microbial genes covered (p = 0.770). Furthermore, no significant differences were observed in alpha-diversity, beta-diversity, the number of taxa identified at each taxonomic level, and the relative abundance of taxonomic units. Discussion These two sample collection methods do not affect microbial population structures within fecal samples and collecting fecal samples directly from the litterbox within 6 hours after defecation can be considered a reliable approach for microbiome research.